Russian Contribution to the International Kant Studies from the Late 19th Century until the Present Day: An Analysis of Publications in “Kant-Studien” - Alexey Salikov (Con-textos Kantianos: International Journal of Philosophy, 2016)
This article gives a general characteristic of the publications of the Russian philosophers in the oldest Kantian Journal “Kant-Studien”. The study embraces the entire period of the existence of this magazine, from the very beginning down to our days. In general, after compiling all materials related to Russia published in “Kant-Studien”, I became aware of get a picture of a significant presence of Russian philosophers in this periodical. This gives me a good reason to conclude that even if the impact of the Russian philosophical thought on the international Kant studies was not decisive, then, at least, it was tangible. This influence was due to the phenomenon which was later called the “Silver Age of Russian philosophy”, as well as the phenomenon of Russian emigration, arising as a result of wars and revolutions in Russia and the exodus of the Russian philosophers of the West, where one of their main initial shelters was Germany.